Analisis Perbandingan Efisiensi Bank Umum Konvensional dan Bank Umum Syariah di Indonesia - Azizah Kartika Rahmawati; S. R. Kartika Sari; Herry Hermawan (Department of Accounting-Faculty of Economic and Business (FEB), 2019)
The purpose of this study was to determine the level of efficiency between conventional commercial banks and Islamic commercial banks. The sampling technique used in this study was purposive sampling by taking state-owned banks and Islamic commercial banks with the highest assets. Efficiency measurement in this study uses the Data Envelopment Analysis (DEA) method. The results of this study indicate that there are differences in efficiency between conventional commercial banks and Islamic commercial banks. Overall, each bank has an efficiency level of 93.67% (conventional commercial banks) and 99.99% (Islamic commercial banks). These results indicate that Islamic commercial banks are more efficient than conventional commercial banks.